PENGEMBANGAN MAJALAH KEBERAGAMAN BUDAYA (MAGADA) BERBASIS KEARIFAN LOKAL BANGKA BELITUNG SEBAGAI SUMBER BELAJAR PADA MATA PELAJARAN IPS DI KELAS IV SD NEGERI PANGKALPINANG - Yurdayanti; Nurjanah (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study is to provide deficiencies in the teaching process in the classroom, especially to make effective, effective learning media to build the national character and love for the homeland of students who are more active. The benefits of this research can provide learning resources that can be considered as reference materials for cultural diversity that are compiled based on the potential of Bangka Belitung local wisdom, and can shape student behavior with character through learning resources in the form of media based on Bangka Belitung local wisdom that touches everyday life. This research method uses a design developed by ADDIE which is an addition to Analysis, Design, Development, Implementation, and Evaluation. The results of this study are: (1) Products with cover components, preface, table of contents, contents that have been in the real world, students in the form of interesting pictures, quiz puzzles, and bibliography. (2) The feasibility level of media expert validation with a proportion of 85.33% in the very appropriate category, material expert validation in 92.38% in the very appropriate category, linguists with a proportion of 96.00% in the very appropriate category. (3) The level of practicality is very practical as evidenced by the results of the response from the teacher with a percentage of 93% in the very practical category, the response from the results of a limited-scale trial with a total of 5 students with a percentage of 86.67% in the very practical category, the response from the results of the field trial with a total of 20 students with a percentage of 87,31% very practical category.